2008
DOI: 10.3130/aije.73.807
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Scales (Specific and Unspecific Sensation Vote) on the Evaluation of the Experimental Combined Environment

Abstract: Regression analysis was applied to the experimental data obtained from the different environmental conditions and proce-Regression analysis was applied to the experimental data obtained from the different environmental conditions and procedures to investigate the difference of scales; the dependent variables were thermal sensation vote (specific scale), the impres-dures to investigate the difference of scales; the dependent variables were thermal sensation vote (specific scale), the impression of hot-cold(unsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In terms of whether the above findings are due to the actual gazing at colors, the results of eye movement measurements showed that the gazing time and frequency rates tended to be higher for cold colors when the thermal sensation was warmer and for warm colors when the thermal sensation was cooler (Sakamoto et al,2007;. Matsubara et al ( , 2011, Shimada et al (2008Shimada et al ( , 2019, and others have shown that the slope of the regression equation is smaller when visual and auditory environmental factors are added than when they are not, when a linear regression of the relationship between temperature and various thermal reports is conducted, and it is speculated that this is because the attentional resources allocated to the thermal environment are smaller.…”
Section: Findings Of Multisensory Studies Related To Thermal Sensationmentioning
confidence: 99%
“…In terms of whether the above findings are due to the actual gazing at colors, the results of eye movement measurements showed that the gazing time and frequency rates tended to be higher for cold colors when the thermal sensation was warmer and for warm colors when the thermal sensation was cooler (Sakamoto et al,2007;. Matsubara et al ( , 2011, Shimada et al (2008Shimada et al ( , 2019, and others have shown that the slope of the regression equation is smaller when visual and auditory environmental factors are added than when they are not, when a linear regression of the relationship between temperature and various thermal reports is conducted, and it is speculated that this is because the attentional resources allocated to the thermal environment are smaller.…”
Section: Findings Of Multisensory Studies Related To Thermal Sensationmentioning
confidence: 99%